NASAL BREATHING AND THERMOREGULATION (REVIEW OF THE LITERATURE) - Levitska, S. A.; Gozhenko, A. I.; Shuhtin, V. V.; Bobrik, L. M.; Babalik, O. Ph. (Journal of Education, Health and Sport, 2015)
Levitska S. A., Gozhenko A. I., Shuhtin V. V., Bobrik L. M., Babalik O. Ph. Носове дихання і терморегуляція (огляд літератури) = Nasal breathing and thermoregulation (review of the literature). Journal of Education, Health and Sport. 2015;5(3):303-310. ISSN 2391-8306. DOI: 10.5281/zenodo.16496 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A303-310 https://pbn.nauka.gov.pl/works/552272 http://dx.doi.org/10.5281/zenodo.16496 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. НОСОВЕ ДИХАННЯ І ТЕРМОРЕГУЛЯЦІЯ (ОГЛЯД ЛІТЕРАТУРИ) nasal breathing and thermoregulation (review of the literature) С. А. Левицька, А. І. Гоженко, В. В. Шухтін, Л. М. Бобрик, О. Ф. Бабалик S. A. Levitska, A. I. Gozhenko, V. V. Shuhtin, L. M. Bobrik, O. Ph. Babalik Буковинський державний медичний університет, м. Чернівці НДІ медицини транспорту, м. Одеса Bukovinian state medical university, Chernivtsi Ukrainian Research Institute for Medicine of Transport, Odesa Article In the article modern literature data on the role of nasal breathing in air conditioning processes and thermoregulation. Keywords: nasal breathing, thermoregulation. Резюме У статті наведені сучасні дані літератури про роль носового дихання в процесах кондиціонування повітря і терморегуляції. Ключові слова: носове дихання, терморегуляція.